2020
DOI: 10.24215/18536387e028
|View full text |Cite
|
Sign up to set email alerts
|

Aceleración y estabilización: disparidad en la tendencia de obesidad en escolares de la provincia de La Pampa (Argentina) entre 1990 y 2016

Abstract: A pesar de los esfuerzos de diversos organismos para reducir la obesidad, sólo algunos países desarrollados muestran una desaceleración o estabilización de su prevalencia. Este trabajo presenta las tendencias en el índice de masa corporal (IMC) y las prevalencias de sobrepeso (SP) y obesidad (OB) ocurridas en escolares entre 1990 y 2016, y su distribución socioeconómica. Se compararon tres encuestas transversales realizadas en 1990, 2005/07 y 2015/16 en escolares primarios de Santa Rosa (La Pampa, Argentina). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Although EW (considering both overweight and obesity) was greater in C2 than C1, the biggest difference was found in the age range group of girls below the median AgM (12 years old), with markedly inter-cohort increases, particularly in obesity. This coincides with the observed child and adolescent obesity registered in Argentina, where EW was informed as the prevalent malnutrition condition (Bejarano et al, 2019;Cesani et al, 2022;ENNyS2, 2019;Orden, 2023;Orden et al, 2021). Likewise, logistic regression results indicated a greater probability of M in girls with EW.…”
Section: Discussionsupporting
confidence: 88%
“…Although EW (considering both overweight and obesity) was greater in C2 than C1, the biggest difference was found in the age range group of girls below the median AgM (12 years old), with markedly inter-cohort increases, particularly in obesity. This coincides with the observed child and adolescent obesity registered in Argentina, where EW was informed as the prevalent malnutrition condition (Bejarano et al, 2019;Cesani et al, 2022;ENNyS2, 2019;Orden, 2023;Orden et al, 2021). Likewise, logistic regression results indicated a greater probability of M in girls with EW.…”
Section: Discussionsupporting
confidence: 88%
“…Overweight, instead, increased in Buenos Aires and remained relatively constant in Mendoza and Misiones. In this regard, Orden et al (2021) reported a decelerating trend of overweight and an accelerating trend of obesity between 1990, 2005–07 and 2015–16 cohorts of schoolchildren from La Pampa. In agreement with these results, the increment of obesity prevalence between C1 and C2 currently found (8%–9% in Buenos Aires and Misiones and close to 5% in Mendoza) suggests that the Argentinian school population has not yet reached a plateau or even a decreasing pattern of overweight and obesity like that found in many developed countries (Wabitsch et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This stabilization was attributed to a cumulative effect of growing population concern about childhood obesity and continued family, school, and government effort to prevent it by encouraging increased physical activity, reduced television viewing and nonfood consumption of sugarsweetened soft drinks by children (Keß et al, 2017;Olds et al, 2011;Yang et al, 2019). However, this trend was not as evident in developing countries or in low-income populations (Bustamante et al, 2021;de Onis et al, 2010;Orden et al, 2021;Ulijaszek et al, 2017), where changing eating habits towards a healthier diet is more costly and, therefore, the prevalence of overweight and obesity continues to increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation